Magnesium alloy with pre-rolling deformation composite electric pulse and aging treatment and preparation method thereof
Patent Information
- Application Number
- CN202611106890.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的是提供预轧制变形复合电脉冲及时效处理的镁合金,解决了现有镁合金热处理工艺能耗高、周期长、易导致晶粒粗化,以及单一处理后强度与塑性难以协同提升的问题
(1)本发明通过预轧制变形引入大量的位错、孪晶等缺陷结构,为后续电脉冲处理提供变形储存能与组织准备。在300℃/40%的预轧制条件下,非基面滑移的激活与变形储存能的显著增加,为后续电脉冲处理的再结晶形核提供了良好的能量基础与微观组织准备。
Smart Images

Figure CN122979722A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alloy material preparation technology, specifically relating to magnesium alloys pre-rolled, deformed, composite electric pulse, and aged treatment, and also to a method for preparing such magnesium alloys. Background Technology
[0002] Wrought magnesium alloys, as the lightest structural metal materials, have broad application prospects in aerospace, transportation, and other fields due to their high specific strength and specific stiffness. However, due to the HCP crystal structure of magnesium alloys, there are few open slip systems at room temperature, resulting in poor plastic deformation capacity. Furthermore, deformation leads to severe work hardening and residual internal stress, typically requiring subsequent heat treatment for microstructure control and performance optimization. While traditional solution treatment and aging treatment can improve the strength and plasticity of materials to some extent, prolonged high-temperature treatment is not only energy-intensive, time-consuming, and inefficient, but also easily causes microstructure coarsening, leading to deterioration of mechanical properties.
[0003] Electrical pulse treatment, as a novel method for treating metallic materials, can achieve microstructure optimization effects such as grain refinement and second-phase regulation in a very short time due to its unique electroplastic effect, demonstrating significant advantages in improving microstructure. However, single pulse current treatment often sacrifices some strength while improving plasticity, making it difficult to achieve a synergistic improvement in strength and plasticity. Currently, systematic research combining pre-deformation with electrical pulse treatment and aging treatment is still insufficient, and the synergistic influence of various process parameters on the evolution of alloy microstructure and mechanical properties is not yet clear. Furthermore, existing magnesium alloy heat treatment processes are energy-intensive, have long cycles, easily lead to grain coarsening, and it is difficult to achieve a synergistic improvement in strength and plasticity after a single treatment. Summary of the Invention
[0004] The purpose of this invention is to provide a magnesium alloy that has undergone pre-rolled deformation combined with electrical pulse and aging treatment, which solves the problems of high energy consumption, long cycle, easy grain coarsening, and difficulty in synergistic improvement of strength and plasticity after single treatment in existing magnesium alloy heat treatment processes.
[0005] Another object of the present invention is to provide a method for preparing magnesium alloys subjected to pre-rolled deformation combined with electrical pulse and aging treatment.
[0006] The technical solution adopted in this invention is a pre-rolled deformed composite electric pulse and aging treated magnesium alloy, which is composed of the following components by mass percentage: Al 6.23%, Zn 1.42%, with the balance being Mg and unavoidable impurities.
[0007] The invention is further characterized by: The room temperature tensile strength of the magnesium alloy is not less than 301 MPa, the yield strength of the magnesium alloy is not less than 190 MPa, and the elongation of the magnesium alloy is not less than 18.5%.
[0008] Another technical solution adopted in this invention is a method for preparing magnesium alloys subjected to pre-rolled deformation combined with electrical pulse and aging treatment, comprising the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment and then cooled to obtain magnesium alloy.
[0009] Another feature of the technical solution of this invention is that: In step 1, the chemical composition of the magnesium alloy ingot is Al 6.23% and Zn 1.42% by mass percentage, with the remainder being Mg and unavoidable impurities; the heat treatment temperature is 410~430℃, the heat treatment time is 12~24h, and the heat treatment is carried out under an argon protective atmosphere to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at grain boundaries generated during the casting process.
[0010] In step 2, the ingot is polished to a smooth and flat surface using metallographic sandpaper of 400# to 2000# to avoid stress concentration during rolling. The specific process of multi-pass rolling is as follows: the reduction amount in each pass is 10%. Before rolling, the smooth and flat magnesium alloy ingot is kept at 280~320℃ for 18-22 minutes. After each rolling deformation, it is kept at 3~7 minutes. After 4 passes of rolling, a rolled magnesium alloy sheet with a total deformation of 40% is obtained.
[0011] In step 3, the rolled magnesium alloy is first cut into strip-shaped samples along the rolling direction, and then polished with 400# to 2000# sandpaper until the surface is smooth to remove the oxide film caused by the rolling process. The sample is then fixed on the electric pulse device with copper clamps to ensure that the current direction is consistent with the rolling direction. During the electric pulse treatment, the pulse width is 0~2000µs, the pulse voltage is 0~20V, the frequency is 1.0~2.0Hz, and the treatment time is 6~10min. In step 3, the electrical pulse treatment refines the average grain size from 64µm in the rolled state to 33µm, and also reduces the β-Mg content. 17 Al 12 The second phase changed from elongated to granular, and the length-to-length ratio decreased from 10.8 to 3.2; XRD showed β-Mg17 Al 12 The diffraction peak intensity decreased and shifted to the right by approximately 0.3°. EBSD showed that the texture intensity extremum decreased from 14.64 μd to 10.31 μd, and some grains showed... <0001> The shaft deflects by approximately 32°.
[0012] In step 4, the alloy after electrical pulse treatment is held at 180~220℃ for 22~26h, and then cooled by air cooling.
[0013] In step 4, during the aging process, β-Mg 17 Al 12 The second phase preferentially nucleates at grain boundaries and twin boundaries, and then precipitates in large quantities within the grains. The precipitated phase at grain boundaries is larger than that within the grains, and the precipitated phase within the grains exhibits a discontinuous precipitate morphology. After aging for 24 hours, the area fraction of the second phase increases from 0.38% in the electric pulse state to 9.2%, and the strengthening contribution of the second phase increases from 2.28 MPa to 55.2 MPa. After aging for 24 hours, the strengthening contribution of grain boundaries is 58.2 MPa, the strengthening contribution of dislocations is 15.9 MPa, the strengthening contribution of solid solution is 48.5 MPa, and the total strengthening contribution is 177 MPa, which differs from the measured yield strength of 190 MPa by 13 MPa.
[0014] In step 4, the room temperature tensile strength of the magnesium alloy is not less than 301 MPa, the yield strength of the magnesium alloy is not less than 190 MPa, and the elongation of the magnesium alloy is not less than 18.5%.
[0015] The beneficial effects of this invention are: (1) This invention introduces a large number of defect structures such as dislocations and twins through pre-rolling deformation, providing deformation storage energy and microstructure preparation for subsequent electrical pulse treatment. Under the pre-rolling conditions of 300℃ / 40%, the activation of non-basal slip and the significant increase in deformation storage energy provide a good energy basis and microstructure preparation for recrystallization nucleation in subsequent electrical pulse treatment.
[0016] (2) This invention uses electrical pulse treatment to replace the traditional high-temperature, long-term solution treatment. At an extremely short time (8 min) and a relatively low temperature (maximum measured temperature 113℃), it effectively promotes grain refinement, second-phase dissolution, and spheroidization, significantly optimizing the microstructure of the material. Comparative isothermal heat treatment experiments show that this effect is mainly attributed to the non-thermal effect of the pulsed current (electron wind reduces the atomic diffusion activation energy) rather than simple Joule heating. This method significantly reduces the processing temperature and time, offering significant advantages of low cost and high efficiency.
[0017] (3) The present invention forms a supersaturated solid solution by electrical pulse treatment, and then combines it with subsequent aging treatment (200℃ / 24h) to realize the second phase (β-Mg). 17 Al 12The precipitates are fine and uniform, achieving an optimal dispersion distribution. The strengthening contribution of the second phase significantly increases from 2.28 MPa in the electric pulse state to 55.2 MPa, becoming the most important factor in the strength improvement of the aged sample; at the same time, the uniformly distributed precipitates effectively alleviate local stress concentration and improve the plasticity of the material.
[0018] (4) The high-strength and high-toughness magnesium alloy prepared by this invention achieves peak comprehensive mechanical properties, with a room temperature tensile strength of 301 MPa, a yield strength of 190 MPa, and an elongation of 18.5%, realizing a synergistic improvement in strength and plasticity. Compared with the single electric pulse treatment state, the tensile strength and yield strength increased by 4.9% and 6.1% respectively, and the elongation increased by 30.3%; compared with the traditional rolled state, the elongation increased by 110%. Attached Figure Description
[0019] Figure 1 These are X-ray diffraction patterns of the AZ61 magnesium alloy samples in the rolled state and after electrical pulse treatment in Example 6 of this invention; Figure 2 This is the EBSD analysis IPF plot of the AZ61 magnesium alloy rolled sample in Example 6 of this invention; Figure 3 This is the EBSD pole plot of the AZ61 magnesium alloy rolled sample in Example 6 of this invention; Figure 4 This is the inverse pole figure of the EBSD analysis of the AZ61 magnesium alloy rolled sample in Example 6 of this invention; Figure 5 This is the EBSD analysis IPF plot of the sample after AZ61 electrical pulse treatment in Example 6 of this invention; Figure 6 This is the EBSD pole plot of the sample after AZ61 electrical pulse treatment in Example 6 of the present invention; Figure 7 This is the EBSD inverse pole figure of the sample after AZ61 electrical pulse treatment in Example 6 of the present invention; Figure 8 This is a tensile fracture morphology image of AZ61 magnesium alloy after electrical pulse treatment in Embodiment 6 of the present invention; Figure 9 These are SEM images of the AZ61 magnesium alloy after electrical pulse treatment and aging treatment in Embodiment 6 of the present invention; Figure 10 This is an OM microstructure diagram of AZ61 magnesium alloy at different rolling temperatures in Comparative Example 1 of this invention; Figure 11 This is a diagram showing the engineering stress-strain curves of AZ61 magnesium alloy under different electrical pulse widths in Comparative Example 2 of this invention. Figure 12This is a diagram showing the engineering stress-strain curves of AZ61 magnesium alloy under different electrical pulse voltages in Comparative Example 2 of this invention. Figure 13 This is an OM microstructure diagram of AZ61 magnesium alloy after isothermal heat treatment in Comparative Example 3 of the present invention. Figure 14 This is a statistical diagram of the second phase of AZ61 magnesium alloy after isothermal heat treatment in Comparative Example 3 of the present invention. Figure 15 This is a SEM microstructure of AZ61 magnesium alloy before isothermal heat treatment in Comparative Example 3 of this invention. Figure 16 This is a SEM microstructure of AZ61 magnesium alloy after isothermal heat treatment in Comparative Example 3 of the present invention. Figure 17 This is a comparison chart of the volume fraction and length ratio of the second phase under different aging times in Comparative Example 4 of this invention; Figure 18 This is an engineering stress-strain curve of AZ61 magnesium alloy under different aging times in Comparative Example 4 of this invention; Figure 19 These are fracture morphology diagrams of AZ61 magnesium alloy under different aging times in Comparative Example 4 of this invention. Detailed Implementation
[0020] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0021] The pre-rolled deformed composite electric pulse and aging treated magnesium alloy provided by this invention is composed of the following components by mass percentage: Al 6.23%, Zn 1.42%, with the balance being Mg and unavoidable impurities. The magnesium alloy has a room temperature tensile strength of not less than 301 MPa, a yield strength of not less than 190 MPa, and an elongation of not less than 18.5%.
[0022] The present invention provides a method for preparing a pre-rolled, deformed, composite electric pulse and aging treated magnesium alloy, comprising the following steps: S1. Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment at a temperature of 410~430℃ for 12~24h, followed by water quenching. S2. Pre-rolling deformation: The magnesium alloy ingot obtained in S1 is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations at a rolling temperature of 300℃ and a rolling deformation amount of 40% to obtain rolled magnesium alloy. S3. Electrical pulse treatment: The rolled magnesium alloy obtained in S2 is cut into strip-shaped samples along the rolling direction and polished smooth, and then subjected to electrical pulse treatment. The parameters of the electrical pulse treatment are: pulse width 1750µs, pulse voltage 15V, frequency 1.5Hz, and treatment time 8min. S4. Aging treatment: The magnesium alloy after the electrical pulse treatment obtained in S3 is subjected to aging treatment at a temperature of 200℃ for 24 hours and air cooling to obtain a high-strength and high-toughness magnesium alloy.
[0023] In S1 above, the magnesium alloy is a wrought magnesium alloy containing aluminum and zinc elements. The chemical composition of the magnesium alloy by mass percentage is: Al: 6.23%, Zn: 1.42%, with the remainder being Mg and unavoidable impurities.
[0024] In the above S1, the preferred temperature for homogenization heat treatment is 420℃, and the preferred time is 12h.
[0025] In the above S2, the specific process of multi-pass rolling deformation is as follows: the reduction amount in each pass is 10%, the sample is kept at 300℃ for 20 minutes before rolling, and kept at 5 minutes after each rolling deformation. After 4 passes of rolling, a sample with 40% deformation is obtained.
[0026] In the above S3, when performing electrical pulse processing, it is necessary to ensure that the current direction is consistent with the rolling direction.
[0027] Example 1 The method for preparing magnesium alloys by pre-rolling deformation combined with electrical pulse and aging treatment proposed in this embodiment includes the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment and then cooled to obtain magnesium alloy.
[0028] Example 2 The method for preparing magnesium alloys by pre-rolling deformation combined with electrical pulse and aging treatment proposed in this embodiment includes the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; In step 1, the chemical composition of the magnesium alloy ingot is Al 6.23% and Zn 1.42% by mass percentage, with the remainder being Mg and unavoidable impurities; the heat treatment temperature is 410~430℃, the heat treatment time is 12~24h, and it is carried out under an argon protective atmosphere to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at grain boundaries generated during the casting process. Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment and then cooled to obtain magnesium alloy.
[0029] Example 3 The method for preparing magnesium alloys by pre-rolling deformation combined with electrical pulse and aging treatment proposed in this embodiment includes the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; In step 1, the chemical composition of the magnesium alloy ingot is Al 6.23% and Zn 1.42% by mass percentage, with the remainder being Mg and unavoidable impurities; the heat treatment temperature is 410~430℃, the heat treatment time is 12~24h, and it is carried out under an argon protective atmosphere to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at grain boundaries generated during the casting process. Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. In step 2, the ingot is polished to a smooth and flat surface using metallographic sandpaper of 400# to 2000# to avoid stress concentration during rolling. The specific process of multi-pass rolling is as follows: the reduction amount in each pass is 10%. Before rolling, the smooth and flat magnesium alloy ingot is held at 280~320℃ for 18-22 minutes. After each rolling deformation, it is held at 3~7 minutes. After 4 passes of rolling, a rolled magnesium alloy sheet with a total deformation of 40% is obtained. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment and then cooled to obtain magnesium alloy.
[0030] Example 4 The method for preparing magnesium alloys by pre-rolling deformation combined with electrical pulse and aging treatment proposed in this embodiment includes the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; In step 1, the chemical composition of the magnesium alloy ingot is Al 6.23% and Zn 1.42% by mass percentage, with the remainder being Mg and unavoidable impurities; the heat treatment temperature is 410~430℃, the heat treatment time is 12~24h, and it is carried out under an argon protective atmosphere to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at grain boundaries generated during the casting process. Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. In step 2, the ingot is polished to a smooth and flat surface using metallographic sandpaper of 400# to 2000# to avoid stress concentration during rolling. The specific process of multi-pass rolling is as follows: the reduction amount in each pass is 10%. Before rolling, the smooth and flat magnesium alloy ingot is held at 280~320℃ for 18-22 minutes. After each rolling deformation, it is held at 3~7 minutes. After 4 passes of rolling, a rolled magnesium alloy sheet with a total deformation of 40% is obtained. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; In step 3, the rolled magnesium alloy is first cut into strip-shaped samples along the rolling direction, and then polished with 400# to 2000# sandpaper until the surface is smooth to remove the oxide film caused by the rolling process. The sample is then fixed on the electric pulse device with copper clamps, ensuring that the current direction is consistent with the rolling direction. During the electric pulse treatment, the pulse width is 0~2000µs, the pulse voltage is 0~20V, the frequency is 1.0~2.0Hz, and the treatment time is 6~10min. In step 3, the electrical pulse treatment refines the average grain size from 64µm in the rolled state to 33µm, and also reduces the β-Mg content. 17 Al 12 The second phase changed from elongated to granular, and the length-to-length ratio decreased from 10.8 to 3.2; XRD showed β-Mg 17 Al 12 The diffraction peak intensity decreased and shifted to the right by approximately 0.3°. EBSD showed that the texture intensity extremum decreased from 14.64 μd to 10.31 μd, and some grains showed... <0001> The shaft deflects by approximately 32°; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment and then cooled to obtain magnesium alloy.
[0031] Example 5 The method for preparing magnesium alloys by pre-rolling deformation combined with electrical pulse and aging treatment proposed in this embodiment includes the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; In step 1, the chemical composition of the magnesium alloy ingot is Al 6.23% and Zn 1.42% by mass percentage, with the remainder being Mg and unavoidable impurities; the heat treatment temperature is 410~430℃, the heat treatment time is 12~24h, and it is carried out under an argon protective atmosphere to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at grain boundaries generated during the casting process. Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. In step 2, the ingot is polished to a smooth and flat surface using metallographic sandpaper of 400# to 2000# to avoid stress concentration during rolling. The specific process of multi-pass rolling is as follows: the reduction amount in each pass is 10%. Before rolling, the smooth and flat magnesium alloy ingot is held at 280~320℃ for 18-22 minutes. After each rolling deformation, it is held at 3~7 minutes. After 4 passes of rolling, a rolled magnesium alloy sheet with a total deformation of 40% is obtained. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; In step 3, the rolled magnesium alloy is first cut into strip-shaped samples along the rolling direction, and then polished with 400# to 2000# sandpaper until the surface is smooth to remove the oxide film caused by the rolling process. The sample is then fixed on the electric pulse device with copper clamps, ensuring that the current direction is consistent with the rolling direction. During the electric pulse treatment, the pulse width is 0~2000µs, the pulse voltage is 0~20V, the frequency is 1.0~2.0Hz, and the treatment time is 6~10min. In step 3, the electrical pulse treatment refines the average grain size from 64µm in the rolled state to 33µm, and also reduces the β-Mg content. 17 Al 12 The second phase changed from elongated to granular, and the length-to-length ratio decreased from 10.8 to 3.2; XRD showed β-Mg 17 Al 12 The diffraction peak intensity decreased and shifted to the right by approximately 0.3°. EBSD showed that the texture intensity extremum decreased from 14.64 μd to 10.31 μd, and some grains showed... <0001> The shaft deflects by approximately 32°; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment, followed by cooling, to obtain a magnesium alloy; In step 4, the alloy after electrical pulse treatment is held at 180~220℃ for 22~26h, and then cooled by air cooling. In step 4, during the aging process, β-Mg17 Al 12 The second phase preferentially nucleates at grain boundaries and twin boundaries, and then precipitates in large quantities within the grains. The precipitated phase at grain boundaries is larger than that within the grains, and the precipitated phase within the grains exhibits a discontinuous precipitate morphology. After aging for 24 hours, the area fraction of the second phase increases from 0.38% in the electric pulse state to 9.2%, and the strengthening contribution of the second phase increases from 2.28 MPa to 55.2 MPa. After aging for 24 hours, the strengthening contribution of grain boundaries is 58.2 MPa, the strengthening contribution of dislocations is 15.9 MPa, the strengthening contribution of solid solution is 48.5 MPa, and the total strengthening contribution is 177 MPa, which is 13 MPa different from the measured yield strength of 190 MPa. In step 4, the room temperature tensile strength of the magnesium alloy is not less than 301 MPa, the yield strength of the magnesium alloy is not less than 190 MPa, and the elongation of the magnesium alloy is not less than 18.5%.
[0032] Example 6 The method for preparing magnesium alloys by pre-rolling deformation combined with electrical pulse and aging treatment proposed in this embodiment includes the following steps: (1) Homogenization treatment: The AZ61 magnesium alloy ingot is placed in a heating furnace and homogenized under an argon protective atmosphere. The temperature is 420℃ and the time is 12h. After the treatment, it is taken out and water quenched to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at the grain boundary generated during the casting process. (2) Pre-rolling deformation: The AZ61 magnesium alloy ingot obtained in step (1) is polished with metallographic sandpaper of 400 to 2000# until the surface is smooth and flat to avoid stress concentration during rolling. Then, it is rolled and deformed in multiple passes using a rolling mill. The rolling temperature is set at 300℃. Before rolling, the sample is kept at 300℃ for 20 minutes. The reduction amount in each pass is 10%. After each rolling deformation, it is kept at 5 minutes. After 4 passes of rolling, a rolled magnesium alloy plate with a total rolling deformation of 40% is obtained. (3) Electrical pulse treatment: The rolled magnesium alloy obtained in step (2) is cut into strips of 1mm×5mm×35mm along the rolling direction. The strips are polished with 400# to 2000# sandpaper until the surface is smooth to remove the oxide film caused by the rolling process. The samples are fixed on the electrical pulse equipment with copper clamps, ensuring that the current direction is consistent with the rolling direction, and then subjected to electrical pulse treatment. The parameters of the electrical pulse treatment are: pulse width 1750µs, pulse voltage 15V, frequency 1.5Hz, and treatment time 8min. During the treatment, the sample temperature is measured using a K-type thermocouple, and the highest measured temperature is 113℃. (4) Aging treatment: The sample after the electrical pulse treatment obtained in step (3) is placed in a drying oven for aging treatment. The aging temperature is 200℃ and the aging time is 24h. After the treatment is completed, it is cooled by air cooling to obtain a high-strength and high-toughness magnesium alloy.
[0033] The high-strength and high-toughness magnesium alloy prepared in this embodiment was characterized by its microstructure and tested for its mechanical properties. After the electrical pulse treatment in step (3), the average grain size of the sample was significantly refined from 64µm in the rolled state to 33µm, and the grain size distribution range was reduced to 1~90µm, with about 90% of the grain size distributed in the 1~60µm range. Static recrystallization was more complete, and the grains were fine and uniformly distributed. With the increase of pulse width, the degree of dissolution of the second phase gradually increased, and the spheroidization effect became more significant. The second phase of the rolled sample without electrical pulse treatment was mainly distributed in elongated and granular shapes, with a length-to-short ratio of 10.8. When the pulse width increased to 1750µs, the degree of dissolution of the second phase was further improved, the morphology was mainly granular, the length-to-short ratio decreased to 3.2, and the area fraction decreased significantly. After electrical pulse treatment, the tensile strength of the sample was 287MPa, the yield strength was 179MPa, and the elongation was 14.2%, which was 61.4% higher than that of the rolled state.
[0034] After aging treatment in step (4), the bright white phase in the tissue was identified as β-Mg by EDS and XRD results. 17 Al 12 The aging treatment significantly affects the precipitation behavior of the second phase. The untreated sample exhibits a relatively small number and larger size of the second phase. After aging for 24 hours, the second phase further precipitates, reaching an optimal dispersion distribution. The area fraction of the second phase increases from 0.38% in the pulsed state to 9.2%. After aging, the size of the precipitates at grain boundaries is significantly larger than that within the grains, indicating that the second phase preferentially nucleates at grain boundaries. The smaller size of the precipitates within the grains, exhibiting a discontinuous precipitation morphology, allows these fine, dispersed particles to more effectively hinder dislocation movement. The magnesium alloy obtained in this embodiment achieves peak comprehensive mechanical properties, with a room temperature tensile strength of 301 MPa, a yield strength of 190 MPa, and an elongation of 18.5%, realizing a synergistic improvement in both strength and plasticity.
[0035] The strengthening mechanism of the high-strength and high-toughness magnesium alloy prepared in this embodiment was quantitatively analyzed. For example... Figure 1 The figure shows the X-ray diffraction patterns of AZ61 magnesium alloy samples in the rolled state and after electrical pulse treatment. The figure also shows the β-Mg after electrical pulse treatment. 17 Al 12 The diffraction peak intensity of the phase decreased significantly, and the overall XRD diffraction peaks showed a rightward shift of approximately 0.3°, indicating that more Al elements dissolved into the α-Mg matrix. Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7The figure shows the EBSD analysis IPF plots, pole figures, and inverse pole figures of AZ61 magnesium alloy samples in the rolled state and after electrical pulse treatment. The figures show that the extreme value of texture intensity decreased from 14.64 mud to 10.31 mud after electrical pulse treatment, and some grains... <0001> The axis deflected by approximately 32°, effectively weakening the original base texture. For example... Figure 8 As shown, the tensile fracture morphology of AZ61 magnesium alloy after electrical pulse treatment is illustrated. The figure shows a significant reduction in the size of the cleavage planes at the fracture surface, and an increase in the number, size, depth, and uniform distribution of dimples, indicating that sufficient plastic deformation occurred in the sample during tensile testing. Figure 9 As shown in the attached figure, the SEM microstructure of AZ61 magnesium alloy after electropulse treatment and aging treatment is presented. The figure shows that after aging treatment, the precipitates at grain boundaries are larger, while the intragranular precipitates are smaller, exhibiting a discontinuous precipitate morphology with fine, dispersed particles uniformly distributed. This indicates that the increase in yield strength of the sample after aging treatment mainly depends on second-phase strengthening and dislocation strengthening. Calculations using the formula show that the area fraction of the second phase in the electropulse state (EPT-2) is 0.38%, and its second-phase strengthening contribution is approximately 2.28 MPa. After aging treatment, the area fraction of the second phase increases to 9.2%, and the second-phase strengthening contribution significantly increases from 2.28 MPa to 55.2 MPa, becoming the most significant factor in the strength improvement after aging. Simultaneously, the grain boundary strengthening contribution slightly decreases from 61.9 MPa to 58.2 MPa; the dislocation strengthening contribution slightly decreases from 18.1 MPa to 15.9 MPa; and the solid solution strengthening contribution decreases from 73.1 MPa to 48.5 MPa. The above-mentioned strengthening mechanism contributes a total of 177 MPa to the strength of the aged specimen, which is 13 MPa less than the actual yield strength of 190 MPa. The high degree of agreement further confirms the reliability of the data in this invention.
[0036] Comparative Example 1 (Comparison of the effects of pre-rolling temperature and deformation) To verify the rationality of the pre-rolling process parameters in step (2) of this invention, Comparative Example 1 was set up. The specific steps are the same as in Example 6, except that the pre-rolling process parameters in step (2) are different.
[0037] (1) Effect of different rolling temperatures: The deformation amount was set as the limit deformation amount at each temperature. Rolling was carried out at 20℃, 200℃, 300℃ and 400℃ respectively, followed by the same electrical pulse treatment (1750µs / 15V / 8min).
[0038] When the rolling temperature is 20℃, a large number of coarse lenticular twins and needle twins exist inside the grains of the sample. The average grain size is 127.4µm. After the electrical pulse treatment, the average grain size is reduced to 96µm. Only a small number of recrystallized grains appear at the grain boundaries. Its tensile strength is 277MPa, yield strength is 166MPa, elongation is only 3.3%, and the fracture surface exhibits typical brittle fracture characteristics with large-sized cleavage planes.
[0039] When the rolling temperature is 200℃, a large number of twins and a small number of shear bands appear in the microstructure, and the average grain size increases to 160.5µm. After the electrical pulse treatment, the average grain size decreases to 89µm. Its tensile strength is 256MPa, its yield strength is 143MPa, and its elongation is 7.1%.
[0040] When the rolling temperature is 300℃ (limit deformation 50%), dynamic recrystallization occurs inside the sample, resulting in fine recrystallized grains that are equiaxed or nearly equiaxed, with the average grain size decreasing to 82.9µm. After electrical pulse treatment, the average grain size further decreases to 69µm, and a large number of recrystallized grains appear in the microstructure. Its tensile strength is 263MPa, yield strength is 167MPa, and elongation is 10.7%.
[0041] When the rolling temperature is 400℃, the grains begin to grow, and the average grain size increases to 89.1µm. After the electrical pulse treatment, the average grain size decreases to 72µm, and some grains show abnormal growth. The tensile strength is 254MPa, the yield strength is 139MPa, and the elongation is 10.3%.
[0042] Conclusion: With the increase of rolling temperature, the deformation mechanism of the alloy gradually shifts from twinning and slip to non-basal slip initiation. When the rolling temperature is 300℃, dynamic recrystallization is most complete, providing the best microstructure preparation for subsequent electrical pulse treatment.
[0043] (2) Effect of different rolling deformation amounts: at 300℃, rolling deformation of 30%, 40% and 50% were carried out respectively, followed by the same electrical pulse treatment.
[0044] When the deformation is 30%, fine dynamic recrystallized grains appear near some of the original grain boundaries, with an average grain size of 68µm. After electrical pulse treatment, the average grain size decreases to 50µm, but the degree of recrystallization is low. Its tensile strength is 284MPa, yield strength is 163MPa, and elongation is 10.9%.
[0045] When the deformation was 40%, grain fragmentation intensified, with an average grain size of 64 µm. Subsequent electrical pulse treatment further refined the average grain size to 33 µm. The tensile strength reached 287 MPa, the yield strength reached 200 MPa, and the elongation was 11.4%. These results indicate that under 40% pre-rolling conditions, the material accumulated higher dislocation density and deformation storage energy, resulting in a higher recrystallization driving force during electrical pulse treatment, thus achieving the finest recrystallized grains and ultimately realizing the optimal synergy between strength and plasticity.
[0046] When the deformation is 50%, the average grain size increases to 82µm and the grain size is not uniform; after electrical pulse treatment, the average grain size decreases to 69µm, and its tensile strength is 263MPa, yield strength is 167MPa, and elongation is 10.7%.
[0047] Conclusion: Figure 10 As shown in the OM microstructure diagrams of AZ61 magnesium alloy at different rolling temperatures, the grain size initially decreases and then increases with increasing rolling temperature, while the number of twins gradually decreases, with dynamic recrystallization being most complete at 300℃. Simultaneously, experimental data indicate that the deformation storage energy continuously increases with increasing rolling deformation. When the deformation is 40%, the grain refinement effect is most significant, resulting in a higher dislocation density and a higher recrystallization driving force during electrical pulse treatment, thus achieving the finest recrystallized grains and optimal mechanical properties.
[0048] Comparative Example 2 (Comparison of the Influence of Electrical Pulse Parameters) To verify the rationality of the electrical pulse processing parameters in step (3) of this invention, comparative example 2 was set up. The specific steps are the same as in embodiment 6, except that the electrical pulse parameters in step (3) are different.
[0049] (1) Effect of different pulse widths: Under the conditions of pulse voltage of 15V and processing time of 8min, the pulse widths were set to 1500µs, 1750µs and 2000µs respectively.
[0050] When the pulse width is 1500µs, the temperature at the measuring point is 93℃, and the average grain size decreases from 64µm to 48µm, with only partial static recrystallization occurring. The length-to-short ratio of the second phase is 4.3. Its tensile strength is 291MPa, yield strength is 201MPa, and elongation is 9.4%.
[0051] When the pulse width is 1750µs, the temperature at the measuring point is 113℃, the average grain size is refined to 33µm, and static recrystallization is more complete. The length-to-short ratio of the second phase decreases to 3.2. Its tensile strength is 287MPa, yield strength is 179MPa, and elongation is significantly increased to 14.2%.
[0052] When the pulse width was 2000µs and the temperature at the measuring point was 124℃, the average grain size actually increased to 54µm, with some grains showing significant growth. The second phase essentially transformed into a spherical morphology, and the length-to-short ratio decreased to 1.2. Its tensile strength decreased to 275MPa, its yield strength decreased to 141MPa, and its elongation was 15.1%.
[0053] Conclusion: Figure 11 As shown in the attached figure, the engineering stress-strain curves of AZ61 magnesium alloy under different pulse widths are illustrated. The figure shows the influence of pulse width on the mechanical properties of the material, verifying the optimal performance under the parameters of 1750µs / 15V / 8min. With increasing pulse width, more energy is injected by a single square wave pulse, and the degree of static recrystallization gradually increases. However, excessively high pulse widths (2000µs) can lead to grain growth, which is detrimental to grain refinement. 1750µs is the optimal parameter.
[0054] (2) Effect of different pulse voltages: Under the conditions of pulse width of 1750µs and processing time of 8min, the pulse voltages were set to 10V, 15V and 20V respectively.
[0055] When the pulse voltage is 10V, the temperature at the measuring point is 71℃, the average grain size decreases to 38µm, and the grain size distribution remains uneven. The length-to-short ratio of the second phase decreases to 4.1. Its tensile strength is 247MPa, yield strength is 155MPa, and elongation is 10.1%.
[0056] When the pulse voltage is 15V, the temperature at the measuring point rises to 113℃, the average grain size is refined to 33µm, and the grain distribution is more uniform. The area fraction of the second phase is significantly reduced, and the length-to-short ratio decreases to 3.2. Its tensile strength is 287MPa, yield strength is 179MPa, and elongation is 14.2%.
[0057] When the pulse voltage was 20V, the temperature at the measuring point rose to 149℃, and the thermal effect was significantly enhanced. The average grain size actually increased to 57µm, with most grains exhibiting abnormal growth. The length-to-short ratio of the second phase decreased to 2.8. Its tensile strength was 287MPa, yield strength was 200MPa, and elongation was 11.6%.
[0058] Conclusion: Figure 12 As shown in the attached figure, the engineering stress-strain curves of AZ61 magnesium alloy under different electrical pulse voltages are illustrated. The figure shows the influence of pulse voltage on the mechanical properties of the material, verifying the optimal performance under the parameters of 1750µs / 15V / 8min. Excessively high pulse voltage (20V) leads to enhanced thermal effects, promoting the merging and growth of already formed fine recrystallized grains through grain boundary migration, thus weakening the grain refinement strengthening effect. 15V is the optimal parameter.
[0059] (3) Effect of different pulse times: Under the conditions of pulse width of 1750µs and pulse voltage of 15V, the processing time was set to 4min, 8min and 12min respectively.
[0060] When the pulse duration was 4 minutes, the temperature at the measuring point was 109℃, and the average grain size decreased to 42µm, although a small number of larger original grains still existed. The length-to-short ratio of the second phase was 3.7. Its tensile strength was 272MPa, its yield strength was 163MPa, and its elongation was 13.6%.
[0061] When the pulse duration was 8 minutes, the temperature at the measuring point rose to 113℃, and the average grain size was refined to 33µm. The length-to-short ratio of the second phase decreased to 3.2. Its tensile strength was 287MPa, its yield strength was 179MPa, and its elongation was 14.2%.
[0062] When the pulse duration was 12 min, the temperature at the measuring point rose to 117 °C, but the average grain size actually increased to 41 µm, and the microstructure uniformity decreased slightly. The length-to-short ratio of the second phase decreased to 3.1. Its tensile strength decreased to 263 MPa, yield strength decreased to 158 MPa, and elongation decreased to 13.4%.
[0063] Conclusion: With increasing pulse time, the temperature rise of the sample is relatively small, and the thermal effect of the current is insufficient to drive significant grain boundary migration. The effect of pulse time on the microstructure is relatively small, with 8 min being the optimal parameter.
[0064] Comparative Example 3 (Isothermal Heat Treatment Control Experiment) To reveal the non-thermal effects of electrical pulse treatment other than the Joule heating effect, Comparative Example 3 was set up. A rolled AZ61 magnesium alloy sample with the same condition as in step (2) of Example 6 was selected and subjected to isothermal heat treatment at 113℃ (i.e., the highest measured temperature during the electrical pulse treatment process in Example 6) for 8 min.
[0065] Microstructural characterization showed that the sample did not undergo significant static recrystallization after isothermal heat treatment, and a large number of original grain morphologies were still retained in the microstructure. The morphology of the second phase remained mainly elongated, showing no significant change compared to the rolled state, indicating that the second phase hardly dissolved or spheroidized.
[0066] Conclusion: Figure 13 , Figure 14 , Figure 15 , Figure 16As shown in the attached figure, this microstructure diagram and second-phase statistical diagram of AZ61 magnesium alloy after isothermal heat treatment are presented. The figure shows that under the same temperature (113℃) and time (8 min), isothermal heat treatment did not result in significant recrystallization or second-phase dissolution, proving the existence of the non-thermal effect of the electric pulse. Under the same temperature (113℃) and time (8 min) conditions, simple heat treatment cannot achieve grain refinement and dissolution and spheroidization of the second phase. However, the electric pulse treatment of this invention can induce significant static recrystallization, refining the grain size to 33µm and significantly reducing the area fraction of the second phase. This indicates that the electric pulse treatment is not a simple heating process, but has significant non-thermal effects. The electron wind generated by the high-density pulsed current can directly act on dislocations, providing additional driving force for dislocation movement, promoting dislocation rearrangement and subgrain boundary formation, thereby accelerating recrystallization nucleation; simultaneously, the interaction between electrons and metal atoms can reduce the activation energy of atomic diffusion, increase diffusion flux, accelerate the migration of solute atoms, and thus promote the dissolution of the second phase. Based on thermodynamic analysis, the electric pulse treatment reduces the second-phase dissolution temperature by approximately 230°C by providing additional free energy; based on kinetic analysis, the electron wind reduces the atomic diffusion activation energy and significantly increases the atomic diffusion flux.
[0067] Comparative Example 4 (Comparison of the impact of delivery time) To verify the rationality of the aging parameters in step (4) of this invention, comparative example 4 was set up. The specific steps are the same as in embodiment 6, except that the aging time in step (4) is different. Aging treatments were performed at 200℃ for 6h, 12h, 24h, 36h, and 48h respectively.
[0068] When no aging treatment is performed (0h), the second phase is relatively small in quantity and large in size, with a tensile strength of 287MPa, a yield strength of 179MPa, and an elongation of 14.2%.
[0069] When the aging time is 6 hours, fine second phases begin to precipitate, but their distribution is not yet uniform. The tensile strength is 291 MPa, the yield strength is 185 MPa, and the elongation is 15.1%.
[0070] When the aging time is 12 hours, the precipitation of the second phase is more obvious and the distribution is relatively uniform. The tensile strength is 293 MPa, the yield strength is 187 MPa, and the elongation is 16.2%.
[0071] When the aging time is 24 hours, the second phase further precipitates, reaching the optimal dispersion distribution state, with the area fraction increasing to 9.2%. The tensile strength reaches a peak of 301 MPa, the yield strength reaches a peak of 190 MPa, and the elongation is 18.5%. The fracture morphology shows a significant increase in the number of dimples, a more uniform distribution, and a significant decrease in the size and number of cleavage planes.
[0072] When the aging time is 36 hours, the precipitation of the second phase is close to saturation, and the particle distribution is more uniform. The tensile strength is 291 MPa, the yield strength is 182 MPa, and the elongation reaches a peak of 19.4%.
[0073] When the aging time is 48 hours, the precipitated phase grows larger, changing from granular and fine rod-like structures to coarser short rod-like and granular structures, indicating over-aging. The tensile strength decreases to 290 MPa, the yield strength decreases to 178 MPa, and the elongation decreases to 17.3%.
[0074] Conclusion: Figure 17 , Figure 18 , Figure 19 As shown, where, Figure 17 The figure shows a comparison of the volume fraction and length ratio of the second phase under different aging times. The figure shows that as the aging time increases, the volume fraction of the second phase gradually increases and tends to saturate after 24 hours. At the same time, the length ratio of the precipitated phase gradually decreases and the morphology changes from coarse rod-shaped to fine granular. Figure 18 , Figure 19 The engineering stress-strain curves and fracture morphology diagrams of AZ61 magnesium alloy at different aging times are shown. The figures indicate that with increasing aging time, the strength first increases and then decreases, reaching a peak at 24 hours. The number of dimples on the fracture surface increases significantly, while the number of cleavage planes decreases. This suggests that during the electrical pulse treatment, the second phase dissolves into the α-Mg matrix, forming a highly supersaturated solid solution, providing a strong precipitation driving force for subsequent aging precipitation. The dispersed distribution of the precipitated phase is optimal at 24 hours, achieving the best synergy between strength and plasticity.
[0075] Mechanism analysis: This invention achieves a synergistic improvement in the strength and toughness of AZ61 magnesium alloy through a composite process route of "pre-rolling deformation + electric pulse treatment + aging treatment".
[0076] Pre-rolling deformation introduces a large number of dislocations and twins, increasing the deformation storage energy. Under rolling conditions of 300℃ / 40%, non-basal slip is activated, and dynamic recrystallization proceeds fully, providing a good nucleation basis for subsequent electrical pulse treatment.
[0077] Electrical pulse treatment utilizes the non-thermal effects of high-density pulsed current to promote dislocation rearrangement and subgrain boundary formation through electron wind at an extremely short time (8 min) and a relatively low temperature (113 °C), accelerating static recrystallization and significantly refining the grains. Simultaneously, it lowers the atomic diffusion activation energy, promoting β-Mg... 17 Al 12 The dissolution and spheroidization of the phases form a supersaturated solid solution. EBSD analysis shows that the electrical pulse treatment effectively promotes the transformation from basal slip to non-basal slip, changing the deformation mechanism from basal to non-basal slip. The slip-dominant force shifts to the cylindrical surface Slip, ConicalSlip, Conical<c+a> Ⅰ Slip and Conical Surface<c+a> II. The deformation mode of coordinated slip significantly improves the plastic deformation capacity of the material.
[0078] Aging treatment utilizes the supersaturated solid solution formed by electrical pulses to promote the aging of β-Mg at a relatively low temperature (200℃). 17 Al 12 The second phase preferentially nucleates at grain boundaries and twin boundaries, and precipitates in large quantities within the grains over time. After 24 hours of aging, the precipitated phase reaches its optimal dispersion distribution. These fine and dispersed second-phase particles can effectively bear the load and hinder dislocation movement, increasing the strengthening contribution of the second phase to 55.2 MPa, which becomes the most important factor in improving the strength of the aged specimen. At the same time, the uniformly distributed precipitated phase alleviates local stress concentration and further improves the plasticity of the material.
[0079] In summary, this invention provides deformation energy storage through pre-rolling deformation, utilizes the non-thermal effect of electric pulse treatment to achieve grain refinement and second-phase dissolution in a short time at low temperature, and then achieves fine and dispersed precipitation of the second phase through aging treatment, ultimately producing a high-strength and high-toughness magnesium alloy with a tensile strength of 301 MPa, a yield strength of 190 MPa, and an elongation of 18.5%, which has significant advantages of low cost and high efficiency.
Claims
1. A magnesium alloy pre-rolled, deformed, composite electric pulse, and time-aging treated with electrical pulse, characterized in that, It consists of the following components by mass percentage: Al 6.23%, Zn 1.42%, with the balance being Mg and unavoidable impurities.
2. The magnesium alloy subjected to pre-rolled deformation composite electric pulse and aging treatment according to claim 1, characterized in that, The magnesium alloy has a room temperature tensile strength of not less than 301 MPa, a yield strength of not less than 190 MPa, and an elongation of not less than 18.5%.
3. A method for preparing magnesium alloys subjected to pre-rolled deformation combined with electrical pulse and aging treatment, characterized in that, The magnesium alloy subjected to pre-rolled deformation composite electric pulse and aging treatment according to claim 2 includes the following steps: Step 1, Homogenization treatment: The magnesium alloy ingot is placed in a heating furnace for homogenization heat treatment, followed by water quenching and cooling; Step 2, Pre-rolling deformation: The cooled magnesium alloy ingot is polished until the surface is smooth and flat, and then subjected to multiple rolling deformations to obtain rolled magnesium alloy. Step 3, Electrical pulse treatment: Cut the rolled alloy into strip-shaped samples along the rolling direction and polish them smooth, then perform electrical pulse treatment; Step 4, Aging Treatment: The alloy after electrical pulse treatment is subjected to aging treatment and then cooled to obtain magnesium alloy.
4. The method for preparing a pre-rolled deformed composite electric pulse and aging treated magnesium alloy according to claim 3, characterized in that, In step 1, the chemical composition of the magnesium alloy ingot is Al 6.23% and Zn 1.42% by mass percentage, with the remainder being Mg and unavoidable impurities; the heat treatment temperature is 410~430℃, the heat treatment time is 12~24h, and it is carried out under an argon protective atmosphere to eliminate dendritic segregation and coarse non-equilibrium eutectic structure at grain boundaries generated during the casting process.
5. The method for preparing a pre-rolled deformed composite electric pulse and aging treated magnesium alloy according to claim 4, characterized in that, In step 2, the ingot is polished to a smooth and flat surface using metallographic sandpaper of 400# to 2000# to avoid stress concentration during rolling. The specific process of multi-pass rolling is as follows: the reduction amount in each pass is 10%. Before rolling, the smooth and flat magnesium alloy ingot is kept at 280~320℃ for 18-22 minutes. After each rolling deformation, it is kept at 3~7 minutes. After 4 passes of rolling, a rolled magnesium alloy sheet with a total deformation of 40% is obtained.
6. The method for preparing a magnesium alloy subjected to pre-rolled deformation composite electric pulse and aging treatment according to claim 5, characterized in that, In step 3, the rolled magnesium alloy is first cut into strip-shaped samples along the rolling direction, and then polished with 400# to 2000# sandpaper until the surface is smooth to remove the oxide film caused by the rolling process. The sample is then fixed on the electric pulse device with a copper clamp to ensure that the current direction is consistent with the rolling direction. During the electric pulse treatment, the pulse width is 0~2000µs, the pulse voltage is 0~20V, the frequency is 1.0~2.0Hz, and the treatment time is 6-10min.
7. The method for preparing a pre-rolled deformed composite electric pulse and aging treated magnesium alloy according to claim 6, characterized in that, In step 3, the electrical pulse treatment refines the average grain size from 64µm in the rolled state to 33µm, and also reduces the β-Mg content. 17 Al 12 The second phase changed from elongated to granular, and the length-to-length ratio decreased from 10.8 to 3.2; XRD showed β-Mg 17 Al 12 The diffraction peak intensity decreased and shifted to the right by approximately 0.3°. EBSD showed that the texture intensity extremum decreased from 14.64 μd to 10.31 μd, and some grains showed... <0001> The shaft deflects by approximately 32°.
8. The method for preparing a magnesium alloy subjected to pre-rolled deformation composite electric pulse and aging treatment according to claim 7, characterized in that, In step 4, the alloy after electrical pulse treatment is kept at 180~220℃ for 22~26h, and then cooled by air cooling.
9. The method for preparing a magnesium alloy subjected to pre-rolled deformation composite electric pulse and aging treatment according to claim 8, characterized in that, In step 4, during the aging process, β-Mg 17 Al 12 The second phase preferentially nucleates at grain boundaries and twin boundaries, and then precipitates in large quantities within the grains. The precipitated phase at grain boundaries is larger than that within the grains, and the precipitated phase within the grains exhibits a discontinuous precipitate morphology. After aging for 24 hours, the area fraction of the second phase increases from 0.38% in the electric pulse state to 9.2%, and the strengthening contribution of the second phase increases from 2.28 MPa to 55.2 MPa. After aging for 24 hours, the strengthening contribution of grain boundaries is 58.2 MPa, the strengthening contribution of dislocations is 15.9 MPa, the strengthening contribution of solid solution is 48.5 MPa, and the total strengthening contribution is 177 MPa, which differs from the measured yield strength of 190 MPa by 13 MPa.
10. The method for preparing a pre-rolled deformed composite electric pulse and aging treated magnesium alloy according to claim 9, characterized in that, In step 4, the magnesium alloy obtained has a room temperature tensile strength of not less than 301 MPa, a yield strength of not less than 190 MPa, and an elongation of not less than 18.5%.